La présence de l’auteur dans les rapports de stage : pratiques et formation de formateurs - Valetopoulos, Freiderikos; Dekhissi, Laurie; Lamprou, Effrosyni (Studia Romanica Posnaniensia, 2022)
In the last three decades there has been an increasing interest in the study of the interaction between the author and the reader in written texts. In this paper, we propose to focus on the analysis of the authorial presence in the internship reports. To this end, we analysed a corpus of L1 French students’ internship reports. The occurrences of JE, NOUS and ON allowed us to establish a list of different functions of these pronouns by observing how trainee-writers are using these three pronouns. These observations enabled us to put forward certain hypotheses concerning training of the future language teachers.